If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10q + 9)(q + 6) = 0 Reorder the terms: (9 + 10q)(q + 6) = 0 Reorder the terms: (9 + 10q)(6 + q) = 0 Multiply (9 + 10q) * (6 + q) (9(6 + q) + 10q * (6 + q)) = 0 ((6 * 9 + q * 9) + 10q * (6 + q)) = 0 ((54 + 9q) + 10q * (6 + q)) = 0 (54 + 9q + (6 * 10q + q * 10q)) = 0 (54 + 9q + (60q + 10q2)) = 0 Combine like terms: 9q + 60q = 69q (54 + 69q + 10q2) = 0 Solving 54 + 69q + 10q2 = 0 Solving for variable 'q'. Factor a trinomial. (6 + q)(9 + 10q) = 0Subproblem 1
Set the factor '(6 + q)' equal to zero and attempt to solve: Simplifying 6 + q = 0 Solving 6 + q = 0 Move all terms containing q to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + q = 0 + -6 Combine like terms: 6 + -6 = 0 0 + q = 0 + -6 q = 0 + -6 Combine like terms: 0 + -6 = -6 q = -6 Simplifying q = -6Subproblem 2
Set the factor '(9 + 10q)' equal to zero and attempt to solve: Simplifying 9 + 10q = 0 Solving 9 + 10q = 0 Move all terms containing q to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 10q = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 10q = 0 + -9 10q = 0 + -9 Combine like terms: 0 + -9 = -9 10q = -9 Divide each side by '10'. q = -0.9 Simplifying q = -0.9Solution
q = {-6, -0.9}
| 0.65x+.05(10-x)=.10(-67) | | x+1/5=x-9/2 | | y+2=-2/3(x-1) | | -5(2x-4)=8x | | 2n^2+4n-70=0 | | 5a+3=4+a | | 4(36)+9y=36 | | 6x^2-3x-2=0 | | 2(2x-5)=3(x-2) | | 7y^3-28y=0 | | 2/3a-11=4+a | | 5M-1=-70-151 | | (9x-2)(7x+3)= | | 8n-3=13 | | (10q-3)(q+11)=0 | | 4x+9(36)=36 | | 4=39-9y | | 12=6+2n | | 3(2x-1)+(x-3)=0 | | x(x-9)=15 | | 8=2x-5 | | 6x-75x=100 | | (3q-2)(q-7)=0 | | 3/7x=21 | | 4x^2-44x+112= | | (3p-2)(q-7)=0 | | 1/7/8/9 | | 3x+35x=76 | | 12x=2x | | -2+1=3x-5 | | 2/5h-7=12/5h-2h | | w+1/5=7/8 |